Stress, Hormones & the role of ICT in autism - Sideraki, Angeliki; Papageorgiou, Elisavet; Tsiava, Malvina; Drigas, Athanasios (Technium BioChemMed, 2022)
The aim of this study is to investigate the association of stress with autism spectrum disorder, through recent research data, as well as the effect of hormones on this association. In more detail, in the found literature the following parameters of the examined issue are examined: The association of cognition with stress and relaxation with the balance and interference of hormones in these relationships, in general, the effects of stress on the mental health of subjects, markers found in the blood of people with autism and contribute to the diagnosis of the disorder and what happens if men with autism have elevated androgens. Also studied are the effects of stress on learning and motivation of students belonging to the autism spectrum, fetal estrogen in people with autism in the context of molecular psychiatry, autism spectrum disorders, compounds that disrupt the endocrine system and heavy metals in amniotic fluid, altered steroidogenesis in boys with autism spectrum disorders, and changes in steroid metabolites as an indication of autistic disorder. Also, the factors that lead to oxidative stress are analyzed, which vary such as transferrin and ceruloplasmin levels. At the same time, the important role of ICT in children with autism is presented, as the emotional intelligence of people with autism can be developed through the use of specialized applications, mobile applications, intelligence technicians and robots such as the Kaspar robot that aim to develop mental ability. The operation of virtual reality(VR) and machine learning using algorithms is important.